Coastal inundation risk assessment due to subsidence and sea level rise in a Mediterranean alluvial plain (Volturno coastal plain – southern Italy). (5th November 2017) - Ciro Aucelli, Pietro Patrizio; Di Paola, Gianluigi; Incontri, Pietro; Rizzo, Angela; Vilardo, Giuseppe; Benassai, Guido; Buonocore, Berardino; Pappone, Gerardo
Abstract: Interdisciplinary studies of the last years highlight that the Italian coasts are significantly subject to retreat and to inundation by sea ingression due to natural and anthropic causes. In this study, the effects of future relative sea level have been evaluated for the Volturno River Plain, one of the widest coastal plain in southern Italy. The plain is characterized by high economical and ecological value, for the presence of farm activities, tourist structures and wetland protected zones. The study area is potentially prone to coastal flooding due to its very low topography and because it is affected by a severe subsidence, which emphasize the local effect of sea level rise due to the ongoing climate changes. In accordance with the guidelines of the MEDFLOOD project, the areas prone to inundation in the years 2065 and 2100 have been evaluated by comparing the future topographical information and expected relative sea level scenarios. The local Vertical Ground Displacements have been derived by PS-InSAR processing data whilst the mean values of the scenarios RCP 2.6 and RCP 8.5 provided by the IPCC (2014) have been used as future sea level projections in 2065 and 2100. The PS-InSar data elaboration shows that the area affected by subsidence corresponds to 35% of the Volturno plain and that the annual rate of the phenomenon ranges between −1 and −25 mm/yr. The inundation analysis, based on the classification of the areas in four hazard classes, indicates that in 2065 the zones located below the sea level will increase approximately of 50% respect to the present conditions, while between 2065 and 2100 the increase can be at least of 60% (IPCC, RCP 8.5 scenarios). Considering the socio-economical and ecological exposure, evaluated following the EUROSION project guidelines, the coastal flooding risk maps have been produced. Almost 8.2 km 2 and 14.4 km 2 of the investigated area has to be considered subject to very high marine inundation risk in 2065 and 2100, respectively.